The Application of Exponential Comparison Method and Analytical Hierarchy Process to Analyze Supply Chain Performance - Hendy Tannady; Thomas Dwi Susmantoro; Tessa Hendra (SEULANGA SYSTEM PUBLISHER, 2023)
The purpose of this research is to map the structure of the fruit supply chain, determine the fruit supplier that best meets the criteria, measure the performance of the fruit supply chain management, and recommend improvements to the fruit supply chain management performance. This research uses the descriptive analysis method for mapping fruit supply chain structure, the Exponential Comparison Method (MPE) for selecting the best supplier, the SCOR model, the Analytical Hierarchy Process (AHP), and Snorm de Boer normalization for measuring fruit supply chain management performance in a period of 1 month, as well as a fishbone diagram to recommend performance improvements. Based on the research results, it is known that members of the fruit supply chain consist of 50 suppliers (fruit and packaging), 4 sub-distributors, 240 retail stores, and 800 resellers. Based on the MPE analysis, there are five selected local and imported fruit suppliers. Based on the results of performance measurements, the fruit supply chain management is good, except for two processes, namely procurement and production, so six practices are recommended that can be implemented by the company.